Mental health literacy as a moderator relationship between self-diagnosis and help-seeking behavior in adolescent Posyandu - Aufa, Nisaul; Saniatuzzulfa, Rahmah (Empathy : Jurnal Fakultas Psikologi, 2024)
In the context of rapid societal changes and the digital era, adolescents are increasingly vulnerable to mental health issues, which are often reflected in help-seeking behavior. A significant 34.9% of adolescents exhibit symptoms of mental disorders, yet only 2.6% seek professional help. The establishment of adolescent health posts (Posyandu) serves as a platform for monitoring adolescent health. However, challenges remain due to the low response rates in help-seeking behaviors and limited interest in Posyandu activities. This study aims to examine the relationship between self-diagnosis and help-seeking behavior, moderated by mental health literacy, among adolescents in Posyandu in the city of "Y." The research adopted a quantitative approach, targeting all members of adolescent Posyandu in the city. A purposive sampling method was employed, selecting adolescents aged 10-23 years who were active in the Posyandu, resulting in 114 respondents. Data were collected using scales for help-seeking behavior (α = 0.801), self-diagnosis (α = 0.795), and mental health literacy (α = 0.528). Data analysis was conducted using Chi-Square correlation and PROCESS Macro Hayes version 4.2. The correlation analysis revealed a significant positive relationship between self-diagnosis and help-seeking behavior. Meanwhile, the PROCESS analysis indicated that the interaction between self-diagnosis and mental health literacy negatively affected help-seeking behavior. It can be concluded that while mental health literacy moderates the relationship between self-diagnosis and help-seeking behavior, it does not strengthen this association among Posyandu adolescents in the city of "Y."